The history of radiation therapy (part I) - A. D. Kaprin; Yu. S. Mardinskiy; V. P. Smirnov; S. A. Ivanov; A. A. Kostin; S. A. Polikhov; I. V. Reshetov; A. S. Fatianova; M. V. Denisenko; T. V. Epatova; S. V. Korenev; A. V. Tereshchenko; et al. (Biomedical Photonics, 2019)
In 1903, on the basis of Morozov Institute of the Moscow Imperial University (currently, P. Herzen Moscow Oncology Research Center, a branch of the National Medical Research Radiological Center, Ministry of Health of the Russian Federation), the first specialized unit in Russia was opened – department of radiation therapy of oncological diseases, in which scientific research in the field of medical radiology was officially launched in our country for the first time. The first studies in the field of radiation therapy can be attributed to this period.The article presents a brief summary of the historical development of radiotherapy in the world and in Russia; provides information on the achievements of global importance, fundamental for this scientific field. The activities of leading Russian organizations in the field of radiation therapy are reviewed; names of scientists, doctors and other specialists who have made a significant contribution to its development are provided. The main literature sources relevant to the field are given.The data in this article may be of interest and be useful for biomedical scientists, practicing radiologists and radiotherapists, oncologists, medical and graduate students, interns and other specialists.